Colecionar, desconstruir, rasurar, reescrever: a descrição arquivista em "O Kit de Sobrevivência do Descobridor Português no Mundo Anticolonial" - Sales, Paulo Alberto da Silva (eLyra, 2022)
From the archivist logic of erasure made by rewriting ruled in deconstruction as construction, it intended to read some writing scenes of the book O Kit de Sobrevivência do Descobridor Português no Mundo Anticolonial (2020), by Patrícia Lino, in which is verified a poetic made by irony, hybridism and parody that opposes to the conception of total History. It appears from the injunctive descriptions “what is it/are they” and “how to use/to play” a reflection about the notion of archive as a speech construction made by remnants as well as it is possible to verify in these same constructions the way to relate with objects, images and words built in power relations through different enunciative practices. It is concluded that those intersemiotic objects – images and joke poems – tension elements from the Portuguese past by the delegitimation of crystallized meanings through the new ways of archiving and to think about the poetry-archive relation as post-autonomous constructions.